A Product- and Process-Oriented Tagset for Revisions in Writing. (January 2022) - Conijn, Rianne; Speltz, Emily Dux; Zaanen, Menno van; Waes, Luuk Van; Chukharev-Hudilainen, Evgeny
The study of revision has been a topic of interest in writing research over the past decades. Numerous studies have, for instance, shown that learning-to-revise is one of the key competences in writing development. Moreover, several models of revision have been developed, and a variety of taxonomies have been used to measure revision in empirical studies. Current advances in data collection and analysis have made it possible to study revision in increasingly precise detail. The present study aimed to combine previous models and current advances by providing a comprehensive product- and process-oriented tagset of revision. The presented tagset includes properties of external revisions: trigger, orientation, evaluation, action, linguistic domain, spatial location, temporal location, duration, and sequencing. We identified how keystroke logging, screen replays, and eye tracking can be used to extract both manually and automatically extract features related to these properties. As a proof of concept, we demonstrate how this tagset can be used to annotate revisions made by higher education students in various academic tasks. To conclude, we discuss how this tagset forms a scalable basis for studying revision in writing in depth.